POPULAR MUSIC AND IDENTITY FORMATION AMONG KENYAN YOUTH - Wanjala, Henry; Kebaya, Charles (Journal of Music Research in Africa, 2017)
The role of music in the formation and shaping of identity cannot be gainsaid since music represents an important cultural sphere where identities are affirmed, challenged, torn apart and reconstructed. Many young people use music and musicians that they admire to distinguish themselves from their peers. Thus, the choice of music among the youth often serves as an important marker of the character and nature of identity under construction. Music is meant to be fun, to brighten life, but the development and expression of musical taste can also be a serious statement about one’s identity. Pop music as a genre has had the greatest appeal and impact to the majority of the youth in Kenya. The influence of the medium and its artists on overall identity development is pervasive, complex, and far-reaching in its cultural significance. Grounded in both a historical analysis and a theoretical framework of identity, we interrogate how contemporary pop music shapes and influences identities among Kenyan youth. Using purposively selected contemporary popular music in Kenya, the article provides a textual exegesis of how music uses resources of history, language, and culture in the construction and performance of certain identities.
Keywords: Identity; Popular music; Youth; performance